Understanding Vocabulary for Essay Writing Test at Eleventh Grade Students of SMK Sirajul Falah Bogor - Yani Octafia (Lexeme : Journal of Linguistics and Applied Linguistics, 2020)
The purpose of this study was to describe students' understanding of vocabulary in completing essay writing tests in class XI Sirajul Falah Bogor. In the 2019/2020 academic year. Respondents in this study were students at a vocational school in Bogor. The research method used a qualitative descriptive method, the population in this study were students of class XI Sirajul Falah Middle School in Bogor, equipped with 336 students. The sampling technique in this study used probability sampling techniques. The subjects selected in this study were 22 subjects who were taken randomly in class XI Sirajul Falah. The data aids used were written tests in the form of essays, interviews and questionnaires. To measure the results of students' writing skills using essay writing tests given to students, there are 3 choices of topics written in descriptive essays and choosing one of the topics. The data were obtained through a test of vocational students' essay writing skills. The aspects that assess the assessment written by students are consistency (1). Content Accuracy with Title, (2) Vocabulary Mastery, (3) Sentence Mastery, (4) Unity, and (5) Spelling Usage and Writing. From the results of data analysis, of the 22 respondents whose lowest score was 24 or 3.11%, only 1 student and the highest score was 44 or 5.71% as many as 2 students and the number of students or at most was 4.93%, for 6 students who achieved 38. Thus it can be denied that the students were able to do the vocabulary test quite well, because most of them achieved scores above the average and none of the students scored below the average.